JEJARING AKTOR DALAM PROGRAM RESTORASI GAMBUT DI KABUPATEN KEPULAUAN MERANTI 2021 - Sinaga, Putra Rikki Hilarius; Handoko, Tito (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Large forest and land fires occurred in 2013 in the Meranti Islands Regency. The peatland fires were caused by land clearing and burning by companies and interest groups. The Sungai Tohor Village community suffered huge losses because their sago plantations were also burned down, causing them to lose their livelihoods. The peatland fires also caused conflict between the community and the company.Kebijakan restorasi gambut merupakan kebijakan publik yang dikeluarkan pemerintah dengan tujuan untuk mengatasi masalah kebakaran hutan dan lahan. The policy is stated in statutory regulations (Presidential Regulation No. 1 of 2016 concerning the Peat Restoration Agency) so that it has binding force and is complied with by all members of society in its implementation. In an effort to accelerate the recovery of peatland restoration, it is carried out using rewetting, revegetation and revitalization of the local economy approaches; which in an integrated manner is known as integrated peat restoration. This research uses a qualitative method with a case study approach and descriptive format which aims to explain, summarize various conditions, various situations, or various variables that arise in the community which is the object of this research based on what happened. Data was obtained from all parties concerned, in other words in this study it was collected from various sources Peat restoration concerns parties who have authority or participate in the implementation process which is focused on the network of actors participating in this program as found by parties from the government and parties outside the government such as NGO (Non Government Organizations). The parties in question cannot be separated from the principles of good governance in order to guarantee good principles in implementing public policies. Keywords: Peat Restoration, Good Governance, Actor Network